THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND ADHERENCE TO ANTI-DIABETIC MEDICATION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Rizky Ramadhani Putri; Agung Setiyadi; Puji Astuti Wiratmo (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2025)
Introduction: Diabetes mellitus is a metabolic disorder with hyperglycemia caused by abnormalities in insulin secretion, insulin action, or both. Diabetes mellitus can be controlled if the patient regularly controls it and adheres to treatment to prevent complications. There are several factors that influence compliance, one of which is family support. The purpose of this study was to analyze the relationship between family support and adherence to anti-diabetic medication in patients with type 2 diabetes mellitus.Methods: This study uses a correlational analytic design with a cross-sectional approach. Sampling using the purposive sampling method with a total sample of 70 respondents. The instruments used were the family support questionnaire and the MMAS-8 questionnaire. Data analysis using Spearman rho test.Results: There was a relationship between family support and adherence to taking anti-diabetic medication in type 2 DM patients. Based on the statistical results of family support and adherence to taking anti-diabetic medication (p = 0,020) and the correlation coefficient was 0,277. This result is positive, which means the higher the family support, the greater a person's compliance with taking medication.Conclusion: In this case, family support is important for type 2 DM patients because it will help improve the patient's quality of life and help type 2 DM patients improve treatment adherence.